2022
DOI: 10.1101/2022.08.24.505144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atypical speech production of multisyllabic words and phrases by children with developmental dyslexia

Abstract: Cross-language data show that children with dyslexia are poor at recognizing syllable stress patterns, yet their speech production appears normal, suggesting an unexpected disconnect between speech input and output processes. Here we utilized a novel computerized speech copying task based on the speech amplitude envelope (AE) to investigate this disconnect. Seventy-five children with and without dyslexia copied familiar spoken targets like "Aladdin". Children with dyslexia were significantly worse at producing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…LFP centre frequencies were filtered from 2 to 8 Hz, in 1 Hz steps with a 2 Hz bandwidth, and HFA centre frequencies were filtered from 17.5 Hz to 42.5 Hz, in 5 Hz steps with a 5 Hz bandwidth before a normalised modulation index value was computed for each channel (19,42). The EEG bands were defined as delta (2-4 Hz), theta (4-8 Hz) beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). The channel exhibiting the strongest nMI, within predefined phase and amplitude band groupings (delta/beta, delta/gamma, theta/beta, theta/gamma), was taken forward for further analysis.…”
Section: Phase Amplitude Coupling (Pac)mentioning
confidence: 99%
See 2 more Smart Citations
“…LFP centre frequencies were filtered from 2 to 8 Hz, in 1 Hz steps with a 2 Hz bandwidth, and HFA centre frequencies were filtered from 17.5 Hz to 42.5 Hz, in 5 Hz steps with a 5 Hz bandwidth before a normalised modulation index value was computed for each channel (19,42). The EEG bands were defined as delta (2-4 Hz), theta (4-8 Hz) beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). The channel exhibiting the strongest nMI, within predefined phase and amplitude band groupings (delta/beta, delta/gamma, theta/beta, theta/gamma), was taken forward for further analysis.…”
Section: Phase Amplitude Coupling (Pac)mentioning
confidence: 99%
“…Based on (32), we can expect that individual differences in the theta/delta power ratio for infants may also predict subsequent language development. Furthermore, previous electrophysiological and magnetoencephalography studies testing TS theory with children with dyslexia have revealed a significant role for delta band encoding in both phonological and vocabulary development (3336). Filtered speech interventions that enhance delta-band information also improve the theta-delta oscillatory power ratio during speech listening for dyslexic children (34).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The current study fills this gap regarding TS theory. It is based on a methodology first developed by Keshavarzi et al (2023) to study speech production in developmental dyslexia.…”
Section: Introductionmentioning
confidence: 99%
“…Phonological deficits could be reflected in both speech perception and production in early life (Gerrits & de Bree, 2009;Keshavarzi et al, 2022); however, relatively fewer studies have concerned speech production in RD, presumably because it is challenging to collect evidence in infants/young children for speech production. An alternative is to examine foreign speech perception and production in older children and adults with RD, and to test whether brain activity patterns during these tasks can be reliable markers of RD, which would also facilitate diagnosis of RD.…”
Section: Introductionmentioning
confidence: 99%